Perícia contábil no contexto do processo trabalhista: um estudo sobre a influência do laudo pericial na decisão judicial - Knackfuss, Eduardo Luiz Dieter (Universidade do Vale do Rio dos Sinos, 2010)
The professionals of the accounting area are present in the Labor Court, acting as experts, by the elaboration of the decision accounting expert. In this sense, the present study had as objective analyzes the influence of the decision accounting expert in the judicial decisions of first degree of the Process of the Labor. To understand the relationship between the decision accounting expert and the judicial sentence, they were collected, through photocopies, 37 decisions, in the period elapsed between 2008 and 2009. It was looked for, with that, to extract elements of the variables to allow to identify the use of the accounting in the judicial decisions. The content of the work revealed, starting from the technique content analysis, that the decisions periciais presented in the process of the work they are indeed capable to assist to the needs informacionais of the Magistrates of first instance, in relative subjects to the accounting facts, given his/her relevance in the uttered sentences; (b) he/she was proven that, same being the accounting expertise, prerogative of Accountant properly enabled by CRC, in practice, the judges of the work used to observe this professional norm in the moment of nomination of the accounting experts; (c) it was evidenced, that the Magistrates of first instance of the Justice of the Work, are used of the information presented in the accounting decisions, when these are sufficiently convincing with the elements joined to the solemnities, being the formal structure of the decision factor certainly of smaller relevance for the driver judicial prolatar his/her sentence. Finally, it was verified that the fact of a decision it was or no elaborated by qualified professional, it is not shown different in his/her level of effectiveness.
Keywords: Perito-contador; Laudo pericial; Prova pericial contábil; Justiça do trabalho; Expert-accountant; Expert-decision; Proof accounting expert; Labor court; ACCNPQ::Ciências Sociais Aplicadas::Ciências Contábeis